A Critical Review of COVID-19 Pandemic Outbreak in the Restaurant Industry - RAJA, Perumal; RAGHU, Ankathi; KANNAN, R.; SURESH, K.; SIVAKAMI, V.; ARMSTRONG, I. Hiller (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
Food Service Industry (FSI) was one of the hardest hit during the outbreak of COVID-19 as they were shutdown to control the spread of the virus across society. The COVID-19 pandemic almost nullified the organized and unorganized restaurant business across the country. Dining out is one of the most popular social activities in a metropolitan city like Coimbatore (popularly known as Manchester of South India), the city has branches of popular restaurant chains from across the globe. Measures such as lockdown, social distancing, and dine-in restrictions adopted by the government to slow down the spread of the virus, have imparted huge loss to the FSI that has in turn severely affected the livelihood of millions of restaurant workers in the country with Coimbatore being no exception. In this background, the authors have studied the case of impact of COVID-19 on restaurants with special reference to Coimbatore. Primary data from restaurants were used for this study. The findings based on the data provide a significant contribution to the FSI, and identify the factors that need to be tapped to frame a strategy to increase the sales volume in upcoming pandemic-like situations. Also, the authors have suggested following the Standard Operating Procedure (SOP) instructed by the government even after the pandemic.